2016
DOI: 10.1097/fbp.0000000000000161
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of context on psychomotor sensitization to ethanol and cocaine

Abstract: Repeated drug injections lead to sensitization of their stimulant effects in mice, a phenomenon sometimes referred to as drug psychomotor sensitization. Previous studies showed that sensitization to cocaine is context dependent as its expression is reduced in an environment that was not paired with cocaine administration. In contrast, the effects of the test context on ethanol sensitization remain unclear. In the present study, female OF1 mice were repeatedly injected with 1.5 g/kg ethanol to test for both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…For instance, the way in which subjects from each age group respond to novelty seems to be involved in the ontogenetic transition from ethanol-induced sensitization to tolerance during infancy. Both the acute stimulation and the sensitized locomotor response induced by ethanol are highly dependent on novelty (Arias et al, 2009a;Didone et al, 2015;Hoshaw and Lewis, 2001;Meyer et al, 2005). Although we did not manipulate novelty in our study, other authors have reported that on PD 15 of the rat there is a peak in the locomotor response to a novel open-field (Campbell and Raskin, 1978), precisely the day on which we tested our subjects trained during the 2nd week, which could influence the expression of sensitization.…”
Section: Discussionmentioning
confidence: 87%
“…For instance, the way in which subjects from each age group respond to novelty seems to be involved in the ontogenetic transition from ethanol-induced sensitization to tolerance during infancy. Both the acute stimulation and the sensitized locomotor response induced by ethanol are highly dependent on novelty (Arias et al, 2009a;Didone et al, 2015;Hoshaw and Lewis, 2001;Meyer et al, 2005). Although we did not manipulate novelty in our study, other authors have reported that on PD 15 of the rat there is a peak in the locomotor response to a novel open-field (Campbell and Raskin, 1978), precisely the day on which we tested our subjects trained during the 2nd week, which could influence the expression of sensitization.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, disturbances of synaptic plasticity properties in dorsal hippocampus CA1 may have direct impact on the NAc core activity and thus in locomotor or relapse processes linked to addiction. Because sensitization is a context‐dependent and or novelty/familiarity‐dependent phenomenon (Didone et al, ), it is possible that hippocampal plasticity may play an important role in this phenomenon and the fact LTD is lacking in resistant mice may thus explain, at least in part, the resistance to behavioral sensitization. LTD is known to be involved in novelty acquisition, including the learning context (Dong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Swiss mice were injected with 2.5 g/kg ethanol whereas DBA/2J mice were injected with 2.0 g/kg ethanol. These doses were selected as the optimal doses for inducing ethanol sensitization in these two strains of mice on the basis of previously published studies [4,9,10,18,20,21]. Pilot studies from our laboratory also confirmed slight differences between strains of mice in the proper ethanol doses to obtain a significant behavioral sensitization (unpublished data).…”
Section: Methodsmentioning
confidence: 93%
“…The same experimental protocol was used in all experiments to induce and test the behavioral sensitization to ethanol in the two strains of mice. The experimental protocol was adapted from previous ethanol sensitization studies from our laboratory [3,4,9]. On the first day of the experiment (P0, acclimation session), mice were acclimated to the apparatus and experimental procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation